Predictors of psychological well being of undergraduate students at the Kulliyyah of Education, IIUM - Gimhani, Sachindra; Ismail, Nik Ahmad Hisham; Abd Hamid, Siti Rafiah; Abd Karim, Aishah Hanim (Global Academic Excellence, 2025)
This study aims to investigate the relationship between test anxiety and psychological well-being among undergraduate students at the Kulliyyah of Education, International Islamic University Malaysia. This study was guided by three objectives: (1) to identify the level of test anxiety among KOED undergraduate students, (2) to determine the psychological well-being among KOED undergraduate students, and (3) to examine the relationship between test anxiety and psychological well-being of undergraduate students. The quantitative method was used in this research, whereby data was collected from 275 undergraduate students at KOED, IIUM, through a random sampling technique. The data were thus analysed considering the research objectives and questions using descriptive statistics, correlation, independent sample t-tests, and ANOVA. The main results showed that test anxiety was a strong predictor of low well-being. The study recommends that students should be actively involved in self-regulation, adopt effective strategies in managing test anxiety, and apply them to enhance their psychological well-being